2016
DOI: 10.1186/s12934-016-0478-7
|View full text |Cite
|
Sign up to set email alerts
|

Subtilisin QK-2: secretory expression in Lactococcus lactis and surface display onto gram-positive enhancer matrix (GEM) particles

Abstract: BackgroundPurified from the supernatant of Bacillus subtilis QK02 culture broth, Subtilisin QK-2 is a type of effective thrombolytic reagent that has great exploitable potential. However, the unbearable flavor that occurs with fermentation and the complicated methods that are required to obtain pure products limit the application of this enzyme. Lactic acid bacteria (LAB)-based delivery vehicles are promising as cheap and safe options for medicinal compounds. The secretory expression and surface display using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Antigens fused to streptococcal protein anchor enable them to be docked onto the peptidoglycan of GEM particles, which was also shown to elicit an immune response in nasally immunized mice [35]. A similar approach was also employed recently for subtilisin QK-2 using GEM [36]. The drawback of this system, however, is that the lactococcal cells are merely a carrier of the displayed protein, not a factory producing the proteins, thus repeated introduction of proteins displayed on lactococcal cells may be needed.…”
Section: The Lactococcal Molecular Toolboxmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigens fused to streptococcal protein anchor enable them to be docked onto the peptidoglycan of GEM particles, which was also shown to elicit an immune response in nasally immunized mice [35]. A similar approach was also employed recently for subtilisin QK-2 using GEM [36]. The drawback of this system, however, is that the lactococcal cells are merely a carrier of the displayed protein, not a factory producing the proteins, thus repeated introduction of proteins displayed on lactococcal cells may be needed.…”
Section: The Lactococcal Molecular Toolboxmentioning
confidence: 99%
“…This suggested a possible role for L. lactis as a cell factory for colorectal cancer therapeutics [88]. Other examples of therapeutics produced using L. lactis as a microbial cell factory include subtilisin QK-2 as an anti-thrombotic agent [36], BT crystal protein Cry5B as an anthelminthic [89], heat shock protein (hsp) 65-6IA2P2 against type 1 diabetes [90] and many others as summarized in Table 2.…”
Section: Lactococcus Lactis As a Cell Factorymentioning
confidence: 99%
“…First, researchers revealed that subtilisin QK-2 (QK) was successfully separated using GEM surface display technology. In detail, QK-LysM, as a fusion protein, was loaded onto GEM particles by the LysM domain [18]. In other studies, a similar strategy was used to successfully attach various viral antigens, including porcine circovirus type two cap protein [15] and porcine epidemic diarrhea virus N protein [7], to GEM particles.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids used in these studies have pSH71-based replicons with the Usp45 signal peptide sequence for protein secretion fused with the gene of interest, and the addition of three LysM repeats in the surface-displayed version. The surface displayed proteins in L. lactis were considered more stable and with higher bioactivity than the secreted counterparts [ 57 , 58 ]. In a different study from Ma et al [ 59 ], the authors administered to chicken live L. lactis expressing cytoplasmic, secreted or surface anchored Eimeria tenella 3-1E protein.…”
Section: Plasmid Vectors Available For Plasmid Dna and Recombinantmentioning
confidence: 99%